2014
DOI: 10.1088/0031-9155/59/13/3637
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular strain and its pattern estimated from cine CMR and validation with DENSE

Abstract: Measurement of local strain provides insight into the biomechanical significance of viable myocardium. We attempted to estimate myocardial strain from cine cardiovascular magnetic resonance (CMR) images by using a b-spline deformable image registration method. Three healthy volunteers and 41 patients with either recent or chronic myocardial infarction (MI) were studied at 1.5 Tesla with both cine and DENSE CMR. Regional circumferential and radial left ventricular strains were estimated from cine and DENSE acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 49 publications
3
29
0
1
Order By: Relevance
“…have developed a method of estimating myocardial strain designed to overcome some of the theoretical limitations of feature-tracking, which uses local features, by estimating pixel-wise strain for myocardial deformation incorporating both local and global myocardial features from cine images. Deformation-tracking21 is based on an in-house intensity-based b-spline deformable registration method22. Our prelimary study21 and other studies2324 have demonstrated that deformable image registration methods could be an alternative way to quantify regional LV deformation.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…have developed a method of estimating myocardial strain designed to overcome some of the theoretical limitations of feature-tracking, which uses local features, by estimating pixel-wise strain for myocardial deformation incorporating both local and global myocardial features from cine images. Deformation-tracking21 is based on an in-house intensity-based b-spline deformable registration method22. Our prelimary study21 and other studies2324 have demonstrated that deformable image registration methods could be an alternative way to quantify regional LV deformation.…”
mentioning
confidence: 73%
“…Deformation-tracking21 is based on an in-house intensity-based b-spline deformable registration method22. Our prelimary study21 and other studies2324 have demonstrated that deformable image registration methods could be an alternative way to quantify regional LV deformation.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…In addition, due to lack of 268 patterns/features in cine images, higher uncertainties presents while estimating pixel-wise 269 strain. Gao et al (2014) showed that the regional circumferential strains could be estimated 270 correctly from cine images. However, greater discrepancies exists during the estimation of 271 regional radial strains, and therefore, could not be used in FE modelling (Gao et al, 2015).…”
mentioning
confidence: 99%